Development of a limitless scale-up photobioreactor for highly efficient photosynthesis-based polyhydroxybutyrate (PHB)-producing cyanobacteria. (November 2022) - Lee, Jeong Seop; Sung, Young Joon; Kim, Dong Hun; Lee, Ju Yeon; Sim, Sang Jun
Graphical abstract: Highlights: Semi-automated fabrication system for an easy-to-scale-up photobioreactor (PBR). Baffle and sparger operating conditions were optimized to maximize mass transfer. Areal biomass yield was improved by 21% compared to the existing PBR. The polyhydroxybutyrate (PHB) content of the produced biomass was 29% higher. Scale-up to 2-ton PBR without cultivation performance deterioration. Abstract: Photosynthetic polyhydroxybutyrate (PHB) production is an attractive technology for realizing a sustainable society by simultaneously producing useful biodegradable plastics and mitigating CO2 . It is necessary to establish an economical large-scale photobioreactor (PBR) capable of effectively cultivating photosynthetic microorganisms such as cyanobacteria. A roll-to-roll winding machine/heat-sealer hybrid system for fabricating an easy-to-scale-up PBR was developed in the present study. The baffle design was optimized to facilitate mass transfer within the PBR, and the operating conditions of the gas sparger were investigated to maximize the CO2 transfer efficiency. The newly developed PBR was able to produce biomass of PHB content 10.7 w/w% at a rate of 6.861 g m −2 d −1, 21 % improved biomass productivity compared with the existing PBR. It was confirmed that biomass productivity was maintained even when PBR was scaled up to 2 tons. Consequently, the newly developed PBR is expected to improve the feasibility of photosynthetic PHB production.